Gas chromatographic analysis of indole alkaloids from Tabernaemontana hilariana - Cardoso, CAL; Vilegas, Wagner [UNESP]; Pozetti, G. L. (Elsevier B.V., 1997)
A fast and efficient procedure was elaborated to identify the alkaloid constituents from Tabernaemontana hilariana (Apocynaceae). The strategy based on fractioning of the crude alkaloid fraction in small silica cartridges followed by thin-layer chromatography (TLC), capillary gas chromatography-flame ionization detection as well as high-resolution gas chromatography-mass spectrometry afforded voacangine, coronaridine, ibogamine, voacangine pseudoindoxyl, voacangine hydroxyindolenine, 3-hydroxycoronaridine and 3-(2-oxopropyl)coronaridine. (C) 1997 Elsevier B.V. B.V.
Keywords: Tabermaemontana hilariana; alkaloids